The Impact of Adaptive Learning Models on Students’ Mathematical Problem-Solving Skills - Nuriyati Hamzah (Fakultas Ilmu Pendidikan dan Budaya - Universitas Bina Mandiri Gorontalo, 2025)
Adaptive learning is an approach that adjusts learning materials, instructional strategies, and levels of difficulty based on students’ characteristics. In mathematics learning, this approach is important because students’ conceptual understanding and problem-solving abilities remain relatively low due to uniform conventional instruction. This study aims to analyze the effect of an adaptive learning model on senior high school students’ mathematical conceptual understanding. The study employed a quantitative approach using a quasi-experimental posttest-only control group design. The research subjects consisted of sixty senior high school students divided into an experimental group and a control group. The research instrument was an essay test based on five indicators of mathematical conceptual understanding. Data were analyzed using an independent samples t-test after meeting the assumptions of normality and homogeneity. The results showed that the data were normally distributed and had homogeneous variances. The t-test yielded a t-value of 4.587 with a significance level of 0.000. These results indicate a significant difference between the experimental and control groups. The mean conceptual understanding ability of students in the experimental group was higher than that of the control group. These findings confirm that adaptive learning is effective in improving students’ mathematical conceptual understanding.